2006
DOI: 10.3758/bf03193437
|View full text |Cite
|
Sign up to set email alerts
|

Differential effects of amount on temporal and probability discounting of gains and losses

Abstract: In four experiments, we compared the effects of delay, probability, and monetary amount on the subjective value of gains and losses. For delayed gains, smaller amounts were discounted more steeply than larger amounts, whereas the opposite pattern was observed with probabilistic gains. For both delayed and probabilistic losses, however, amount had much smaller and less reliable effects on discounting. Taken together, the pattern of differential magnitude effects leads to delayed gains' being discounted signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

50
295
7
8

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 313 publications
(375 citation statements)
references
References 41 publications
50
295
7
8
Order By: Relevance
“…Our study showed that delayed pain is discounted in a different way than that of the monetary losses that were discounted in previous research (Estle et al, 2006;Ostaszewski & Karzel, 2002;Weatherly & Derenne, 2013). If delayed punishments are higher or equal to immediate ones, as was the case in most of the previous studies on punishment discounting (Estle et al, 2006;Ostaszewski & Karzel, 2002;Weatherly & Derenne, 2013), delayed punishments are always the best choice from the perspective of the participant.…”
Section: Discussionmentioning
confidence: 54%
See 3 more Smart Citations
“…Our study showed that delayed pain is discounted in a different way than that of the monetary losses that were discounted in previous research (Estle et al, 2006;Ostaszewski & Karzel, 2002;Weatherly & Derenne, 2013). If delayed punishments are higher or equal to immediate ones, as was the case in most of the previous studies on punishment discounting (Estle et al, 2006;Ostaszewski & Karzel, 2002;Weatherly & Derenne, 2013), delayed punishments are always the best choice from the perspective of the participant.…”
Section: Discussionmentioning
confidence: 54%
“…If delayed punishments are higher or equal to immediate ones, as was the case in most of the previous studies on punishment discounting (Estle et al, 2006;Ostaszewski & Karzel, 2002;Weatherly & Derenne, 2013), delayed punishments are always the best choice from the perspective of the participant. An interesting question emerges: why are there different preferences for delayed losses and delayed pain if both of them are considered punishment, even though there is no such variability for different reinforcements?…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Why was there then a (small) magnitude effect for losses in two experiments in the former (Estle et al, 2006) study? Possibly in the 50% of the cases when the receipts conditions preceded the payments condition, that primed the subjects to be more sensitive to magnitudes.…”
Section: Disutilitiesmentioning
confidence: 99%